RELATIONSHIP BETWEEN SOCIO-ECONOMIC LEVEL AND TOOTH LOSS IN ELDERLY AGE IN CIREUNDEU VILLAGE - Rheni Safira Isnaeni; Atia Nurul Sidiqa; Najma Hafifah Adhiatma (Journal of Health and Dental Sciences, 2026)
Tooth loss in the elderly is a health problem that has a significant impact on aesthetic function, mastication, and quality of life. Socioeconomic factors, such as education, income, and occupation, contribute to the rate of tooth loss. This study aims to evaluate the relationship between socioeconomic level and tooth loss in the elderly in Cireundeu Village; analytical observational research with a cross-sectional design using primary data taken directly during research activities carried out using the total sampling technique. The analysis was conducted using Fisher's exact test. The study was conducted on 62 elderly respondents (≥60 years old) in Cireundeu Village. The analysis showed that the majority of respondents had a low education level (91.9%) and low income (80.6%). The average number of tooth loss in respondents was 19.92. There is a significant relationship between socioeconomic level and tooth loss; respondents with lower education, income, and no work experience have more tooth loss than respondents with higher socioeconomic levels (p-value <0.05). Socioeconomic level has a significant relationship with tooth loss in the elderly in Cireundeu Village. Low education, income, and not working are factors that can increase the risk of tooth loss. DOI : 10.54052/jhds.v5n3.p267-274